2016
DOI: 10.1002/spe.2420
|View full text |Cite
|
Sign up to set email alerts
|

CloudEyes: Cloud‐based malware detection with reversible sketch for resource‐constrained internet of things (IoT) devices

Abstract: Summary Because of the rapid increasing of malware attacks on the Internet of Things in recent years, it is critical for resource‐constrained devices to guard against potential risks. The traditional host‐based security solution becomes puffy and inapplicable with the development of malware attacks. Moreover, it is hard for the cloud‐based security solution to achieve both the high performance detection and the data privacy protection simultaneously. This paper proposes a cloud‐based anti‐malware system, calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 23 publications
(36 reference statements)
0
47
0
Order By: Relevance
“…The database sources include huge number of the various signatures that classify malicious objects. In the signature-based malware detection, there are some various qualities including fast identification, easy to run, and broadly accessible [27].…”
Section: Signature-based Malware Detectionmentioning
confidence: 99%
“…The database sources include huge number of the various signatures that classify malicious objects. In the signature-based malware detection, there are some various qualities including fast identification, easy to run, and broadly accessible [27].…”
Section: Signature-based Malware Detectionmentioning
confidence: 99%
“…In [21], the authors demonstrated the feasibility of implementing existing device management protocols on resource-constrained devices. A cloud-based algorithm was proposed in [22] to provide privacy service for resource-constrained IoTDs. Finally, the work in [23] investigated how cloud computing can be securely integrated in large-scale IoT systems.…”
Section: Introductionmentioning
confidence: 99%
“…However, such a solution cannot examine the details of activities that are executed in IoT devices, which are important to enable fine-grained detection of IoT malware. Another possible solution is to detect these activities by host-based security mechanisms [2,51]. Unfortunately, IoT devices are usually resource-constrained and always hard to support full-fledged detection solution.…”
Section: Introductionmentioning
confidence: 99%